مضامين صحيفة البصائر وسبل الاستفادة منها في الوقت الراهن - طلحة, الياس (جامعة الوادي - University of Eloued, 2021)
تعالج الدراسة الحالية واحدة من أهم الصحف الاصلاحية التي استطاعت أن تستمر لمدة طويلة في وجه التضييق الاستعماري على الصحف العربية في الجزائر، ألا وهي صحيفة "البصائر" لسان حال جمعية العلماء المسلمين، من خلال العمل على معرفة أهم الموضوعات التي تناولتها في سلسلتها الثانية، وأهم وظائفها، وأشكالها الفنية، والأساليب الاقناعية المستخدمة بهدف استخلاص ما يمكن أن تقدمه من إفادة للمؤسسات الصحفية وابراز كفاحها ودورها الاصلاحي في خدمة الدين الاسلامي واللغة العربية . The current study deals with one of the most important reformist newspapers that were able to last for a long time in face of the colonial restriction on Arab newspapers in Algeria, namely "Al-bassa`ir", the mouthpiece of the Association of Muslim Schol-ars, by working on knowing the most important topics covered in its second series, and the most important Its functions, artistic forms, and persuasive methods used in order to extract the benefits it can provide to the press institution s and highlight their struggle and reform role in serving the Islamic religion and the Arabic language.
دراسة وصفية تحليلية (السنة الثامنة/العدد 317-361) 1955-1956م
مقال
Keywords: صحافة، صحافة إصلاحية، جمعية العلماء المسلمين; journalism, reform journalism, Muslim Scholars Association